Serologic Surveillance for Orthoflaviviruses and Chikungunya Virus in Bats and Opossums in Chiapas, Mexico - J. Manuel Aranda-Coello; Carlos Machain-Williams; Manuel Weber; Alma R. Dzul Rosado; Tyler R. Simpkins; Bradley J. Blitvich (Viruses)
We performed serologic surveillance for selected arthropod-borne viruses (arboviruses) in bats and opossums in the Lacandona Rainforest, Chiapas, Mexico, in 2023–2024. Sera were collected from 94 bats of at least 15 species and 43 opossums of three species. The sera were assayed by the plaque reduction neutralization test (PRNT) for antibodies to eight orthoflaviviruses (dengue viruses 1–4, St. Louis encephalitis virus, T’Ho virus, West Nile virus, and Zika virus) and one alphavirus (chikungunya virus; CHIKV). Twelve (12.8%) bats and 15 (34.9%) opossums contained orthoflavivirus-specific antibodies. One bat (a Jamaican fruit bat) was seropositive for Zika virus, and 11 bats contained antibodies to an undetermined orthoflavivirus, as did the 15 opossums. All bats and most opossums seropositive for an undetermined orthoflavivirus had low PRNT titers, possibly because they had been infected with another (perhaps unrecognized) orthoflavivirus not included in the PRNTs. Antibodies that neutralized CHIKV were detected in three (7.0%) opossums and none of the bats. The three opossums had low CHIKV PRNT titers, and therefore, another alphavirus may have been responsible for the infections. In summary, we report serologic evidence of arbovirus infections in bats and opossums in Chiapas, Mexico.